A Critical Phenomenon in Solitonic Ising Chains - Loutsenko, I.M.; Spiridonov, V.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We discuss a phase transition of the second order taking place in non-local 1D Ising chains generated by specific infinite soliton solutions of the KdV and BKP equations.